A Pragmatic Plan for the Mental Health Consequences During Covid-19 Pandemic Through Ayurveda - Harshitha K.S; Shankar Gautam; Ram Kishor Joshi; Ajay Kumar Sahu (International Journal of Ayurveda and Pharma Research, 2021)
Introduction: Beyond infection, the COVID-19 pandemic has also affected individuals through associated mental illnesses like anxiety and stress and has caused a collateral damage. Ayurveda has described 3 main factors which are responsible for the occurrence of diseases, one of them is Prajnaparadha, which is stated as the main cause for all the mental illness. The threefold treatment principles of Daivavyapashraya, Yuktivyapashraya and Satvavajaya targeting the Ahara, Achara and Chesta is an ideal plan to deal with stress built up in this pandemic. Materials and methods: The Ayurvedic classical textbooks and the peer reviewed articles focusing mental health researches were reviewed. This plan involves the implementation of Daivavyapashraya, Yuktivyapashaya and Satvavajaya based on the exposure and exhibition of symptoms of COVID-19. Daivavyapashraya Chikitsa is employed by Vishnusahasranama recitation/listening, Yuktivyapashraya Chikitsa is employed by the various drugs like Bramhi, Shankapushpi, Ashwagandha etc. and formulations which have psycho-neuro-immune-response, Satvavajaya Chikitsa by the process of counseling. Results and Discussion: The interdependent nature of immunity and psychological state is already well established and it decides the outcome of disorders. An immune response can be largely affected by mental well-being and mental illness can negatively affect its outcome. Conclusion: The three fold treatment plan centering the pshycho-neuro-immune action is a complete health promotive, preventive and curative plan and will certainly help in the revival of mental health in the times and after the COVID-19 pandemic.